Old Wine in New Bottles? An Overview of Two Centuries of Free Trade between the United States and Canada - See, Scott (Maine Policy Review, 2003)
On February 5, 2003 the Maine International Trade Center and University of Maine Canadian American Center co-sponsored a day-long forum on the challenges and opportunities of free trade between Canada and the United States. This article presents the edited remarks of Scott See who gave audience members a whirlwind overview of the history of Canadian-American free trade from the Revolutionary War era up to passage of the Free Trade Agreement in 1989.